The magnitude of the key financial parameters of select companies in indian cotton textile industry - an exploratory evaluation - Vadivel, C.; Gowri, K. (Journal of Contemporary Research in Management (JCRM), 2013)
A major portion of any countryâ€™s gross domestic product is contributed by its corporate sector. India is a country of more than 1000 million people with 3.28 square million kilometers of land and endowed with million kilometers of natural resources. The success of India depends on the performance of the corporations. In this context, the Indian cotton textile industry occupies an important place in the economy of the country because of its contribution to the industrial output, employment generation and foreign exchange earnings. This study has been conducted to analyze the performance of selectedÂ  companies in Indian cotton textile industry. It uses trend analysis, cost analysis, and profitability analysis to examine the performance of seven companies listed in Bombay Stock Exchange. Based on the analysis, it brings out inferences for the cotton textile industry.